The design of cinematic-VR experiences in inducing empathy towards persons with dementia (PWD) in Singapore - Chew, Keng Hao (Nanyang Technological University, 2023)
Singapore is one of the fastest-ageing countries, with a population of 5.5 million, an estimated 40,000 older adults above 60 live with dementia. The figure is projected to increase to 80,000 by 2030 and 187,000 by 2050. Caregiving is integral and correlated to the quality of life for persons with dementia (PWD). Tailored care has also become necessary for individuals whose needs change over time as their condition worsens. Caregivers for PWD often feel overburdened to care for their loved ones with dementia given the irreversible degenerative characteristics and challenging symptoms of dementia. While there are community action plans to empower PWD, limited efforts are put into programmes specifically aimed at inducing empathy towards PWD and understanding its effect on caregivers.